Research synthesis methods
"The journal's scope includes all aspects of research synthesis methods irrespective of discipline or area of application. Papers may address statistical methods, empirical research and simulations, literature retrieval and information science, data extraction, software, graphics and reporting of synthesis results, issues of study quality, reporting or other systematic biases, narrative analysis and synthesis of qualitative data, synthesis of individual participant data, use of synthesis for developing practice guidelines, integration with cost effectiveness or decision analysis, comparison and integration of methods across different disciplines, techniques for application in different environments, applications that illustrate a novel methodology, or other such broadly methodological topics pertinent to conducting or using research synthesis"--Publisher's description.